Analysis of Spray Droplet Nozzle Characteristics on Biodiesel (B35) with Injection Pressure Variations - Syaifularif; Joni Arif; Widarto (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2026)
This study, entitled Analysis of Spray Droplet Characteristics of Nozzle in Biodiesel (B35) under Injection Pressure Variations, investigates the effect of injection pressure on the spray droplet atomization characteristics of Biodiesel B35 and correlates these characteristics with changes in fuel molecular composition determined using Gas Chromatography–Mass Spectrometry (GC–MS). The novelty of this research lies in integrating spray atomization analysis with GC–MS-based molecular characterization to explain how molecular composition influences fuel atomization behavior. An experimental approach was employed using several injection pressure variations in a nozzle system, followed by GC–MS analysis of Diesel B0, Biodiesel B35, and the B0+B35 blend. The GC–MS results revealed that the blended fuel exhibited a broad molecular weight distribution ranging from 106.165 to 843.6107 g/mol, containing both light hydrocarbons, such as O-xylene (C₈H₁₀), and heavy hydrocarbons, such as hexacontane (C₆₀H₁₂₂). Biodiesel B35 showed the highest average molecular weight due to the predominance of fatty acid methyl ester (FAME) compounds, whereas Diesel B0 exhibited the lowest molecular weight because of its higher proportion of light hydrocarbon fractions. The blending process also resulted in stable, reduced, disappeared, and newly formed molecular species, indicating changes in molecular distribution caused by physical interactions between the fuels. These compositional changes affected key fuel properties, including viscosity, volatility, and atomization performance. Spray image analysis demonstrated that increasing injection pressure produced finer and more uniformly distributed droplets, indicating improved atomization quality. The findings demonstrate that the interaction between fuel molecular characteristics and injection pressure plays a significant role in determining spray behavior and has the potential to improve diesel engine combustion efficiency and fuel performance.